IN-VITRO NEPHROPROTECTIVE ROLE OF ETHANOLIC ROOT EXTRACT OF Boerhaavia diffusa AGAINST CISPLATIN-INDUCED NEPHROTOXICITY - Kalaivani M.K; Soundararajan P; Hannah R Vasanthi; Sumathy Arociaswamy (International Journal of Phytomedicine, 2015)
Context and purpose of the study: The present study was carried out to investigate the antioxidant and nephroprotective role of ethanolic root extract of Boerhaavia diffusa (ERE). Results: Antioxidant activity of ERE was studied using DPPH free radical scavenging activity, Nitric oxide scavenging activity and reducing power assay. To study the nephroprotective role of ERE against cisplatin, a porcine renal epithelial cell line (LLC-PK1) was used. Cisplatin increases the apoptotic and necrotic cells and also increases the production of ROS in the treated cells. Co-treatment of ERE decrease the apoptotic and necrotic cells and attenuates the ROS production. This nephroprotective activity could probably be correlated with the phytochemicals like polyphenols (4.5 ±0.02 mg/g), flavonoids (4.2 ±0.08 mg/g) and tannins (6.5 ±0.3 mg/g) present in the extract. Brief summary and potential implications: These findings suggested that toxicity induced by cisplatin could be reduced by the presence of phytoconstituents in the ERE. This study showed that phytoconstituents present in B.diffusa could manage the nephrotoxicity induced by life saving drugs and it can be considered to be given as an adjuvant therapy.